On the distribution and natural history of a rarely encountered species: Goliathus (Fornasinius) klingbeili Zöller, Fiebig, & Schulze, 1995 (Coleoptera: Scarabaeidae: Cetoniinae) - Maquart, P.o.; Malec, P. (Zootaxa, 2017)
Mudge et al. (2012) surveyed the Cetoniinae (Coleoptera: Scarabaeidae) of Ghana and recorded Goliathus (Fornasinius) higginsi Westwood, 1874, but no other species from this subgenus. We add the rare species Goliathus (Fornasinius) klingbeili Zöller, Fiebig, & Schulze, 1995 as a new country record for Ghana from the dense forests of the Volta and Eastern Regions. The species was previously reported as very rare in Togo (Zöller et al. 1995) in the northern dry part of the Bafilo Region. We record that the larvae develop in hyrax (Dendrohyrax dorsalis (Fraser, 1855) (Mammalia: Procaviidae) middens and can be locally common in this microhabitat. The purpose of this note is to record the new distributional and natural history data, discuss the taxonomy and bionomy of the subgenus Goliathus (Fornasinius) Bertoloni, 1852, and provide a key to species.